IMPACT OF SOCIAL NETWORK FACEBOOK MARKETING PREDICTORS ON CUSTOMER PURCHASE INTENTION - Bokhari, Syed Imran Azhar; Ihsan, Dr. Hajra; Jamshaid, Fouzia (The journal of contemporary issues in business and government, 2021)
Social networking sites especially Facebook is being increasingly used by marketers to conduct online promotion activities. Despite being the most important online marketing tool these days, many companies is begun thinking about how utilizing social network. Facebook could help in appealing customer’s attention and to construct a profitable relationship with prospective people. Thus the objective of current research is to examine social network Facebook marketing predictors which help marketers to predict customer’s purchase intention. The current study proposed a conceptual framework and it tested with the cross-sectional data gathered from 300 students who used social network Facebook with the help of a questionnaire. The present study empirically confirmed that social network Facebook marketing predictors are significantly related to customers purchase intention. In the same way, interactivity and information content has a substantial impact on performance expectancy. Moreover, performance expectancy has been shown to have a significant impact on customer purchase intention. The results revealed that performance expectancy while partly mediating the relationships between interactivity and customer purchase intention. Findings of structural equation modeling supported the validity and reliability of current study model. The research results offer various implications on how marketers can effectively plan and implement their ads on social network Facebook.